Dopant-free Oxygen-rich Titanium Dioxide: LED Light-induced Photocatalysis and Mechanism Insight - Jun, Yan Tai; Kah, Hon Leong; Pichiah, Saravanan; Azrina, Abd Aziz (Springer New York LLC, 2017)

(untitled)
In this work, we successfully synthesized visible light-responsive oxygen-rich titanium dioxide (O2–TiO2) photocatalysts. Through hydrothermal decomposition of peroxo-titania complex, the in situ generation of oxygen significantly shifted the light absorption toward visible region. The existence and contribution of oxygen excess defect present in O2–TiO2 was confirmed through FTIR and XPS analysis. The annealing temperature influenced the oxygen content and textural property of O2–TiO2 samples and subsequently their photocatalytic activity. The O2–TiO2 calcined at optimum temperature of 300 °C recorded the highest photocatalytic activity toward methylene blue degradation, approximately 7.3- and 3.2-fold higher than that of commercial P25 and anatase TiO2, respectively. The enhancement was attributed to shortening of band gap and low recombination rate of charge carriers when the oxygen content increased at higher temperature. In addition, O2–TiO2 displayed high reusability rate and good catalytic stability after being evaluated by four consecutive catalytic runs. The reactive radical species responsible for charge transfer mechanism and high photocatalytic activity were hydroxyl radical (·OH), holes and superoxide radical anions (·O2−) after performing multiple scavenging tests.